Study on the applications of two analytical methods for the construction of traveling wave solutions of the modified equal width equation - Yokus, Asif; Durur, Hulya; Nofal, Taher A.; Abu-Zinadah, Hanaa; Tuz, Munevver; Ahmad, Hijaz (De Gruyter Poland Sp Z O O, 2020)
In this article, the Sinh-Gordon function method and sub-equation method are used to construct traveling wave solutions of modified equal width equation. Thanks to the proposed methods, trigonometric soliton, dark soliton, and complex hyperbolic solutions of the considered equation are obtained. Common aspects, differences, advantages, and disadvantages of both analyticalmethods are discussed. It has been shown that the traveling wave solutions produced by both analytical methods with different base equations have different properties. 2D, 3D, and contour graphics are offered for solutions obtained by choosing appropriate values of the parameters. To evaluate the feasibility and efficacy of these techniques, a non-linear evolution equation was investigated, and with the help of symbolic calculation, these methods have been shown to be a powerful, reliable, and effective mathematical tool for the solution of nonlinear partial differential equations.
Keywords: the Sinh-Gordon function method; exact solution; sub-equation method; nonlinear partial differential equation